The Relationship Between Pre-Anesthesia Anxiety and the Incidence of Post-Operative Nausea and Vomiting (PONV) in Patients Undergoing General Anesthesia at Islamic Hospital Purwokerto - Mutia, Lisa; Novitasari, Dwi; Burhan, Asmat (Java Nursing Journal, 2024)
Background: The anaesthetic method employed during surgical procedures may cause pre-anaesthesia apprehension to increase, which is strongly associated with the occurrence of post-operative nausea and vomiting (PONV), which signifies alterations in psychological and physiological responses. Purpose: To examine the correlation between pre-anaesthesia anxiety and the occurrence of post-operative nausea and vomiting among Islamic Hospital Purwokerto patients undergoing general anaesthesia. Implementing Methods: By utilising a total sampling technique and an analytical approach with a cross-sectional design, 59 patients undergoing surgery under general anaesthesia in April 2023 were included. We gathered primary data by administering pre-anesthesia and post-anesthesia PONV questionnaires to patients in the inpatient ward. Findings: Most patients analysed by patient characteristic analysis were between the ages of 36 and 45 (33.90%), female (62.71%), had completed secondary school (54.24%), and were classified as ASA 2 (84.05%). The majority (72.88%) underwent moderate surgery, and all patients received 100% family support. Panic (49.2%), severe anxiety (42.4%), and moderate anxiety (8.5%) were the most prevalent responses. Moderate (6.7%), severe-to-moderate (28.8%), and severe (64.4%) nausea and vomiting were reported by the majority. A significant relationship exists between pre-anaesthesia anxiety and the incidence of post-operative nausea and vomiting (PONV) in patients undergoing general anaesthesia at Islamic Hospital Purwokerto, as indicated by the chi-square statistic = 0.016). Conclusion: The chi-square statistic indicates a significant relationship between pre-anaesthesia anxiety and the incidence of PONV in patients undergoing general anaesthesia at Islamic Hospital Purwokerto.